Hydropower development and the meaning of place. Multi-ethnic hydropower struggles in Sikkim, India. Issue 89 (February 2018) - Dukpa, Rinchu Doma; Joshi, Deepa; Boelens, Rutgerd
Highlights: Contextual politico-historical imaginaries shape and influence people's SOP. Place-people relations, meanings and experiences are non-uniform and dynamic. Hydropower related contestation and indifference has geo-ethnic underpinnings. Development interventions affect people's SOP and vice versa. Exclusionary place-identity privileging some, weakens overall SOP based resistance. Abstract: Academic research and media tend to emphasize the strong opposition to hydropower development in Sikkim, India, and position this as resistance to an environmentally-destructive, trans-local development, particularly by the culturally-rooted, ethnic minority Bhutia and Lepcha communities. There are several accounts of contestations of hydropower development projects in India's Eastern Himalayan States – signifying robust and predictable indigenous people-place connections. Why then, was the implementation of the largest, Teesta Stage III Hydro Electric Project, located in Chungthang Gram Panchayat Unit in North Sikkim, in the heartland of the Bhutia-Lepcha region, not contested? In unraveling this anomaly, our focus is to understand how people-place connections are shaped and differentially experienced. Our findings are that hydropower development has elicited diverse responses locally, ranging from fierce contestation to indifference, to enthusiastic acceptance. The complexity and malleability of "place" and people's "sense of place" provide evidence that indigeneity does not always indicate resistance to large-scale project interventions. In ethnically and socio-politically fractured communities like Chungthang, trans-local developments can reinforce ethno-social divides and disparities, and re-align traditional place-based ethno-centric solidarities along new politically-motivated lines. We argue that linear, one-dimensional views of local social coalescence around place belie more complex relations, which evolve dynamically in diverse socio-cultural and politico-economic contexts.